2021
DOI: 10.1186/s11671-021-03535-w
|View full text |Cite
|
Sign up to set email alerts
|

Alternate-Layered MXene Composite Film-Based Triboelectric Nanogenerator with Enhanced Electrical Performance

Abstract: The output power of the triboelectric nanogenerator (TENG) strongly depends on the performance of triboelectric materials, especially microstructures and functional groups of them. In this work, aiming at the excellent triboelectric ability, alternate-layered MXene composite films-based TENG with abundant fluorine groups(-F) through layer-by-layer stacking are designed and fabricated. Benefitting from the uniform intrinsic microstructure and increased dielectric constant, when the amount of the Nb2CTx nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
11
1
Order By: Relevance
“…Recently, an emerging two-dimensional (2D) nanomaterial, called as MXene, that is, transition metal nitrides, carbides, and carbonitrides, has been reported as promising candidates for TENGs. [103][104][105][106][107][108] MXene is produced by etching Al atom layers from MAX phase, referring to the remaining layers with the general formula of M n+1 X n T x (n = 1-3), in which M represents a transition metal, such as Ti, Sc, Cr, Mo, and etc., X represents carbon or nitrogen, and Tx represents surface terminations (eg, OH, O, and F). [109][110][111][112] Apart from exhibiting a high metallic conductivity, the presence of abundant F groups and terminating functional groups containing oxygen in MXenes provide a highly electronegative surface that suitable for TENGs application.…”
Section: Materials Selection For Tengsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an emerging two-dimensional (2D) nanomaterial, called as MXene, that is, transition metal nitrides, carbides, and carbonitrides, has been reported as promising candidates for TENGs. [103][104][105][106][107][108] MXene is produced by etching Al atom layers from MAX phase, referring to the remaining layers with the general formula of M n+1 X n T x (n = 1-3), in which M represents a transition metal, such as Ti, Sc, Cr, Mo, and etc., X represents carbon or nitrogen, and Tx represents surface terminations (eg, OH, O, and F). [109][110][111][112] Apart from exhibiting a high metallic conductivity, the presence of abundant F groups and terminating functional groups containing oxygen in MXenes provide a highly electronegative surface that suitable for TENGs application.…”
Section: Materials Selection For Tengsmentioning
confidence: 99%
“…Recently, an emerging two‐dimensional (2D) nanomaterial, called as MXene, that is, transition metal nitrides, carbides, and carbonitrides, has been reported as promising candidates for TENGs 103–108 . MXene is produced by etching Al atom layers from MAX phase, referring to the remaining layers with the general formula of M n+1 X n T x (n = 1‐3), in which M represents a transition metal, such as Ti, Sc, Cr, Mo, and etc., X represents carbon or nitrogen, and Tx represents surface terminations (eg, OH, O, and F) 109–112 .…”
Section: Materials Selection For Tengsmentioning
confidence: 99%
“…In addition to the composition with polymers, MXenes can also be composited inorganic materials for use in TENGs. Feng and co-workers 110 reported an alternate-layered MXene composite produced with Nb 2 CT x and Ti 3 CT x . They found that 15 wt % Nb 2 CT x in the composite could lead to the best performance of the TENGs.…”
Section: Inorganic Nanomaterials Used In Tengsmentioning
confidence: 99%
“…In addition to the composition with polymers, MXenes can also be composited inorganic materials for use in TENGs. Feng and co-workers 110 reported an alternate-layered MXene composite produced with Nb 2 CT x and Ti 3 CT x . They found According to the maximum output voltage and current, the 2D materials can be listed in the order of (−) MoS 2 , MoSe 2 , WSe 2 , and WS 2 (+).…”
Section: D Nanomaterialsmentioning
confidence: 99%
“…As an example, Ma’s group reported a stretchable TENG fabricated from 1D cellulose nanofibers (CNFs) integrated with an MXene dispersion as a liquid electrode in conjunction with standard silicon rubber as a triboelectrification layer . However, to the best of our knowledge, there have been few studies of pure MXenes or MXene-rich composites that simultaneously act as effective electrodes and triboelectrification layers (having electronegative or even electropositive characteristics) for high-performance output. Such investigations could be helpful by precisely locating MXenes in the triboelectric series.…”
Section: Introductionmentioning
confidence: 99%